Global detection of glacier surges from surface velocities, elevation change and SAR backscatter data between 2000 and 2024: a test of surge mechanism theories - Gregoire Guillet; Douglas I. Benn; Owen King; David Shean; Erik Schytt Mannerfelt; Romain Hugonnet (Journal of Glaciology)
The systematic investigation of individual glacier surges across a large statistical sample is key to a better understanding of surge mechanisms. This study introduces a consistent framework for identifying glacier surges from diverse remotely sensed datasets: NASA ITS_LIVE velocity fields, glacier thickness changes digital elevation models and surface roughness from SAR backscatter. We combined these diverse datasets using Gaussian process modelling and signal processing approaches to generate the first worldwide inventory of glaciers with active surges between 2000 and 2024, identifying 261 surge events on 246 glaciers. We performed validation against reference data and conducted a quantitative analysis of key surge metrics - surge duration and peak surface velocity. Our results confirm 12 surge-type glaciers in the Randolph Glacier Inventory (v7). We further evaluated climatological influences on the distribution of surge-type glaciers and assessed the predictive capabilities of existing theories for surges, including hydrological and thermal controls as well as the enthalpy balance theory. In addition, we present the first global analysis of velocity time series from individual surge events and discuss terminus-type dependent dynamics. Our findings strongly support the unified enthalpy balance theory in explaining the breadth of observed surge behaviours. Finally, we report new surge onsets in glaciers quiescent since the 19th century.